2014
DOI: 10.1007/s40620-013-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathological profile of biopsied Egyptian children with primary nephrotic syndrome: 15-year single center experience

Abstract: This is the first large study on the pathological pattern of PNS in children from Egypt, and it shows that MCD is the most frequent underlying pathology and steroid resistance is the most frequent indication for biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
7
2
Order By: Relevance
“…It is worth noting that, in this study, the proportion of MN in glomerular diseases increased from 6.1-18.6%, which was much higher than that of children in other countries [11,17,19,20] and higher than that reported by Nie et al, which showed that the proportion of children with membranous nephropathy in China increased from 3-7% [12]. The number of patients with MN in the United States has been decreasing year by year [20].…”
Section: Discussioncontrasting
confidence: 52%
“…It is worth noting that, in this study, the proportion of MN in glomerular diseases increased from 6.1-18.6%, which was much higher than that of children in other countries [11,17,19,20] and higher than that reported by Nie et al, which showed that the proportion of children with membranous nephropathy in China increased from 3-7% [12]. The number of patients with MN in the United States has been decreasing year by year [20].…”
Section: Discussioncontrasting
confidence: 52%
“…It is worth noting that, in this study, the proportion of MN in glomerular diseases increased from 6.1% to 18.6%, which was much higher than that of children in other countries [11,17,19,20] and higher than that reported by Nie et al, which showed that the proportion of children with membranous nephropathy in China increased from 3% to 7% [12]. The number of patients with MN in the United States has been decreasing year by year [20].…”
Section: Discussioncontrasting
confidence: 52%
“…In a cross-sectional study in China, MCD was considered to be the most common glomerular disease in children [12]. In Egypt and South Asia, MCD was reported to be the most common glomerular disease in children [11,17,18]. In Croatia and Italy, IgAN was reported to be the most common glomerular disease in children [10,14].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological patterns in some studies from other geographical locations are presented in (Table 2). [10][11][12][13][14][15] Arif et al 11 Absar et al 12 Bakr et al 13 Asinobi et al 14 Incidence of focal segmental glomerulosclerosis (FSGS) is observed to be increasing over the years in Pakistan. 11,12,15 Geographical variation seems to be significant contributors for the different histopathological findings of nephrotic syndrome in children.…”
Section: Resultsmentioning
confidence: 99%